THE ASSOCIATION BETWEEN MATRIX METALLOPROTEINASE-9 (MMP-9) WITH HIGH SENSITIVE TROPONIN T (hs-TnT) IN PATIENT WITH ACUTE MYOCARDIAL INFARCTION - Suyasa, I Putu Gede Eka Ariawan; Rina, Ketut; Widiana, I Gde Raka (Medicina, 2015)
Mechanism of acute myocardial infarction (AMI) is previously due to atherosclerotic plaque rupturewith occurs because extra-cellular matrix of plaque fibrous cap destruction or degradation by proteaseenzyme matrix metalloproteinase-9 (MMP-9), which released by macrophage cell.Increased plasmaMMP-9 is predisposition factor of atherosclerotic plaque rupture in AMI and followed by acutethrombosis inside coronary artery lumen which caused myocardial ischemic and clinical sign of AMI. Ifthe ischemic process continuous and ongoing that can caused myocardial necrosis which can increasedplasma troponin. High sensitive troponin T (hs-TnT) newly and more sensitive detection of plasmacTn-T than conventional.The aim of this study was to determined the association between plasmaMMP-9 with hs-TnT in AMI patients.This study was a cross-sectional observational which performedin 62 patients with AMI which enrolled by consecutive sampling at Sanglah Hospital Denpasar fromDecember 2011 until December 2012. MMP-9 and hs-TnT plasma level were measured 48 hours afteronset IMA. Sixty two patients AMI were involved in this study consist of 35 STEMI patients (56.5%)and 27 NSTEMI patients (43.5%), the mean plasma MMP-9 was 23.9 (SD 0.42) ng/mL and hs-TnT was464.7 (SD 39.3) ng/mL.The results of this study were positive correlation between MMP-9 and hs-TnTAMI patients (r= 0.507; Y= - 650.6 + 46.7(X1); P<0.0001); plasma MMP-9 and onset of AMI wereinfluenced to plasma hs-TnT with formulationY = - 815.0 + 46.5(X1)+ 20.7(X2); (â MMP-9=46.5(95%CI: 24.7 to 68.4); P<0.0001; â onset AMI=20.7(95%CI : 2.1 to 39.4); P=0.030) and there was more strongercorrelation betweenMMP-9 and hs-TnT in STEMI group than NSTEMI. [MEDICINA 2015;46:22-27].Mekanisme terjadinya infark miokard akut (IMA) didahului oleh proses ruptur plak aterosklerosisdan diawali dengan destruksi atau degradasi matriks ekstraseluler fibrus cap plak oleh enzim proteaseyang dihasilkan sel makrofag yaitu matrix metalloproteinase-9 (MMP-9). Kadar MMP-9 yang meningkatmerupakan faktor predisposisi terjadinya ruptur plak aterosklerosis pada IMA yang diikuti olehproses trombosis akut pada lumen arteri koroner yang menyebabkan proses iskemia miokard dangejala klinis IMA. Proses iskemia yang tidak teratasi akan mengakibatkan nekrosis miokard yangditandai meningkatnya troponin jantung. Pemeriksaan high sensitive troponin T (hs-TnT) merupakanpemeriksaan kadar troponin yang terbaru dan memiliki kemampuan lebih baik dari pemeriksaantroponin konvensional. Tujuan dari penelitian ini untuk mengetahui hubungan kadar MMP-9 denganhs-TnT plasma pada penderita IMA. Penelitian ini merupakan studi observasional potong lintangyang dilakukan pada 62 penderita IMA yang dikumpulkan secara consecutive sampling di RSUPSanglah Denpasar dari Desember 2011 sampai Desember 2012. Kadar plasma MMP-9 dan hs-TnTdiukur 48 jam setelah awitan IMA. Dari 62 sampel penelitian yang terdiri dari 35 pasien STEMI(56.5%) dan 27 pasien NSTEMI (43.5%) didapatkan rerata kadar MMP-9 plasma 23.9 (SB 0.42) ng/mL dan hs-TnT plasma 464.7 (SB 39.3) ng/mL.Hasil penelitian ini terdapat korelasi positif antaraARTIKEL ASLI JURNAL ILMIAH KEDOKTERAN • 23death in the world,1 approximately30% from all cause of death.2Acutecoronary syndrome (ACS) is one ofcoronary heart diseasemanifestation and a seriouscardiovascular emergency.3Basic pathogenesis acutemyocardial infarction isatherosclerotic plaque rupturewith following thrombus formationin coronary artery. The process ofatherosclerotic plaque rupture iscaused by protease enzymereleased from macrophage cell,such as matrix metalloproteinase-9 (MMP-9), that cause degradationand fibrous cap rupture and formthrombus with coagulation cascadeactivation. This thrombusformation will give clinicalmanifestation of ACS and increaseof troponin levels.4-7Cardiac troponin (cTn),cTnTand cTnI , is a gold standardfor detection of myocardialnecrosis.5,8 Using high sensitivecardiac troponin (hs-cTn), hs-TnTand hs-TnI, will improve earlydiagnosis of acute myocardialinfarction (AMI) significantly andhopefully will decrease falsepositive result.5,9Several studies have beendone to compare MMP-9 levelswith hs-TnT in patients with ACS.Kobayashi et al10 found MMP-9levels increased in acute phase ofACS as reflection of plaquevulnerability and hs-TnT levelsincreased in later phase. Setiantoet al11 in 2011 compared MMP-9levels MMP-9 and troponin-I (cTn-I) in ST Elevation MyocardialInfarction (STEMI) and UnstableAngina Pectoris (UAP)/ Non STElevation Myocardial Infarction(NSTEMI) with result a positivecorrelation between increase ofMMP-9 levels and cTn-I mainly inSTEMI group and stated MMP-9role in myocardial damage severitywith r=0.33 and P=0.003. Thereis no research that studycorrelation between increase ofMMP-9 levels and hs-TnT in AMIpatients.METHODSThis study was aobservational study with cross-sectional design to evaluate MMP-9 levels and hs-TnT levels in AMIpatients at emergency unit andIntensive Cardiac Care Unit(ICCU) Cardiology DepartementUdayana University MedicalSchool/ Sanglah Hospital. Thisstudy was a research tree aboutACS that has been held fromDecember 2011 until December2012 and the result became JointStudy of ACS. This study has beenapproved by Ethics Committee ofUdayana University MedicalSchool/Sanglah HospitalDenpasar. Subjects of this studywere 62 patients with AMI thatfulfilled inclusion and exclusioncriteria. The inclusion criteriawere: 1) all AMI patients age 30-80 years old and treated atemergency unit and ICCU SanglahHospital, 2) gave consent toparticipate in this study. Theexclusion criteria were : 1) valvularheart diseases (VHD), 2) congestiveheart failure (CHF), 3) acute orchronic liver disease, 4) chronickidney disease (CKD) (creatinineclearance < 60 ml/1.73 m2/min),5) chronic or acute infection, 6)sepsis, 7) malignancy, 8) treatedwith corticosteroid or nonsteroidal anti inflammatory orimmunosuppresive drugs morethan 1 weeks, and 9) stroke. Thisstudy using human MMP-9 ELISAkit and Roche Elycsys 2010 kitwhich measured 48 hours afteronset AMI.Analysis of correlationbetween MMP-9 with hs-TnTusing non-parametric analysiswith Spearman test (P<0.05).Multivariate analysis withmultiple linear regression therelationship of the functionalpredictive value MMP-9 and othersconfounding variable to plasma hs-TnT. The last we performedANCOVA analysis to determinethe difference of strengthassociation between plasma MMP-9 and hs-TnT in STEMI orNSTEMI group. Data analysisusing SPSS 17 with significantP<0.05.RESULTSA total of 62 samples wereincluded in this study. Matrixmetalloproteinase-9 (MMP-9) andhs-TnT plasma levels 48 hoursafter AMI onset were measured.The samples also got treatmentbased on ACS guideline fromPERKI 2014.12Subject characteristicsTotal 62 patients with AMIwere included, 50 males (80.6%)and 12 female (19.4%), with meanage 57.9 (SD 10.7) years. Thirtyfive patients were diagnosed withSTEMI (56.5%) and 27 patientswith NSTEMI (43.5%) with meanonset between 6.74 (SD 3.8) hours.Cholesterol levels were between110-327 mg/dL, LDL levels werebetween 56.3-244.5 mg/dL, HDLkadar MMP-9 dengan hs-TnT pada penderita IMA dengan kekuatan korelasi sedang dan secarastatistik signifikan (r= 0.507; Y= - 650.6 + 46.7(X1); P<0.0001); kadar MMP-9 plasma dan awitan IMAmempengaruhi kadar hs-TnT plasma pada penderita IMA dengan formula persamaan Y = - 815.0 +46.5(X1)+ 20.7(X2); (â MMP-9=46.5(IK 95% : 24.7 sampai 68,4); P<0.0001; â awitan IMA=20.7(IK 95%: 2.1 sampai 39.4); P=0.030). dan kekuatan hubungan kadar MMP-9 dengan hs-TnT pada kelompokSTEMI lebih besar daripada NSTEMI. [MEDICINA 2015;46:22-27].